Contesting the classroom : reimagining education in Moroccan and Algerian literatures - Twohig, Erin (Contemporary French and francophone cultures, 2019)
Contesting the Classroom explores how Algerian and Moroccan novels depict the postcolonial classroom, and how postcolonial literature has been taught in Morocco and Algeria. It argues that Arabized education has indelibly influenced the development of postcolonial novels, which have a deeply fraught yet endlessly creative relationship to the classroom.